2012
DOI: 10.1007/s00784-012-0767-4
|View full text |Cite
|
Sign up to set email alerts
|

Possible link between Hashimoto's thyroiditis and oral lichen planus: a novel association found

Abstract: Objectives Hashimoto's thyroiditis as well as lichen planus has been associated to a number of disorders, generally of auto-immune origin. A novel possible association between oral lichen planus (OLP) and Hashimoto's thyroiditis (HT) is here proposed on the basis of a cross-sectional survey. Materials and methods One hundred and five unrelated OLP patients were considered. Diagnosis of HT was based on positive serum anti-TPO, anti-Tg, TSH levels and the typical ultrasound pattern of the thyroid gland. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 16 publications
7
47
1
3
Order By: Relevance
“…A novel possible association between OLP and thyroid gland diseases (Hashimoto's thyroiditis) has been proposed recently on the basis of cross-sectional, case-control studies similar to our [11,12]. A very similar odd ratio estimates were found by Siponen et al [11] for the associacion of any thyroid diseases and OLP, particularly with hypothyroidism.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…A novel possible association between OLP and thyroid gland diseases (Hashimoto's thyroiditis) has been proposed recently on the basis of cross-sectional, case-control studies similar to our [11,12]. A very similar odd ratio estimates were found by Siponen et al [11] for the associacion of any thyroid diseases and OLP, particularly with hypothyroidism.…”
Section: Discussionsupporting
confidence: 87%
“…All of the OLP patients in the present study with the coexistence of Hashimoto thyroiditis and all but one in recently reported [12] were female gender. Most autoimmune diseases occurs significantly more frequently in women than men, especially Hashimoto's thyroiditis and Grave's disease, with a female to male ratio of 50:1 and 7:1 respectively [42,43].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations